Non-Muslim Customer Acceptance Behavior Toward Halal Products in Yogyakarta - Muhammad Baehaqi; Ragil Setyo Cahyono; Anton Prasetyo (IQTISHADIA, 2023)
This research aims to generate practical empirical insights into the acceptance behavior of non-Muslim consumers towards halal products in Yogyakarta. The foundational framework employed for this study is Ajzen’s Theory of Planned Behavior (TPB), with the incorporation of determinants such as knowledge and religiosity, along with the integration of habit-related variables. The study was conducted in Yogyakarta Province, considered a microcosm of Indonesia, representing the diversity of subjects relevant to this research. Data was collected from five regencies/cities in Yogyakarta by administering questionnaires and analyzed using the Structural Equation Model (SEM) with the wrapPLS 7.0 application. The findings reveal that all variables positively influence acceptance attitudes and behaviors. Nonetheless, certain variables do not significantly contribute to the outcomes. Acceptance attitudes and behaviors are primarily shaped by the subjective norm variables and planned behavior control, and this aligns with theoretical expectations. The research outcomes establish interpersonal behavior as a suitable model for further development into a behavioral framework for the acceptance behavior of nonMuslim consumers towards halal products. Theoretically, this research initiates a discourse in the domain of consumer behavior theory, specifically in the realm of interpersonal behavior. In practical terms, the findings can aid businesses in tailoring their communication strategies with customers.